Successfully treated with siltuximab and prednisone in a 7-year-old girl with DOCK8-deficiency presenting as recurrent wart-like lesions: a case report - Sun, Zhe; Wei, Ruoqu; Pan, Chaolan; Ni, Cheng; Zhang, Xue; Guan, Wenbin; Cheng, Ruhong; Gu, Yan; Yu, Hong; He, Kejun; Zhang, Zhen; Yu, Xia; et al. (Frontiers in Immunology, 2024)
Dedicator of cytokinesis 8 (DOCK8) deficiency represents a primary immunodeficiency with a wide range of clinical symptoms, including recurrent infections, atopy, and increased malignancy risk. This study presents a case of a 6-year-old girl with DOCK8 deficiency, characterized by severe, treatment-resistant herpetic infections who was successfully treated with siltuximab and glucocorticoids. The successful use of siltuximab in achieving remission highlights the pivotal role of interleukin-6 (IL-6) in DOCK8 deficiency pathogenesis and suggests that IL-6 modulation can be critical in managing DOCK8 deficiency-related viral infections, which may inform future therapeutic strategies for DOCK8 deficiency and similar immunodeficiencies.